Preparation of mechanically robust and autonomous self-healable elastomer based on multiple dynamic interactions. (5th March 2021) - Wang, Minhui; Zhou, Jiahui; Jiang, Xiaolin; Sheng, Yeming; Xu, Min; Lu, Xun
Graphical abstract: Highlights: The elastomer with multiple dynamic interactions was successfully synthesized. The Cu-DMG-SS shows excellent mechanical strength and good self-healing ability. Cu 2+ can accelerate the dynamic covalent bonds exchange reactions. Abstract: Self-healing materials have attracted considerable attention because of their sustainable property of prolonging service life and reducing resource consumption. However, as plenty of room-temperature self-healable materials have been studied, it still remains a great challenge to equip these materials with admirable mechanical strength since there is a compromise between intermolecular interactions and chain mobility. Herein, a novel strategy of integrating self-healing ability with robustness in polymeric elastomer at ambient condition was developed. The synthesized polyurethane was equipped with multiple reversible interactions including disulfide bonds, oxime urethane bonds, H-bonds and coordination interactions, and formed triple cross-linking network. What's important is that Cu 2+ could not only act as the coordination center, but also serve as the catalyst to accelerate disulfide exchange and oxime urethane exchange reaction. XPS and stress relaxation tests revealed that the introduction of CuCl2 reduced the relaxation activation energy of both the disulfide metathesis and oxime urethane exchange reaction. Thanks to the multiple interactions design and the effects of Cu 2+, the elastomer was endowed with excellent mechanical strength of 19.5 MPa and self-healing efficiency of 83% at room temperature.